P1774 Myocardial work indices in adult patients with repaired aortic coartation. (17th January 2020) - Timoteo, A T; Moura Branco, L; Galrinho, A; Ilhao Moreira, R; Sousa, L; Agapito, A; Cruz Ferreira, R
Abstract: Background: Myocardial strain analysis is a tool that allows a more precise assessment of cardiac performance. However, strain is relatively load dependent. New tools have been developed, with afterload adjustment. It was our objective to assess myocardial work (MW) in patients with repaired aortic coartation (ACo). Methods: Study of consecutive adult patients with corrected ACo submitted to a routine transthoracic echocardiogram in 2018 at our centre. Patients with an aortic valve prosthesis, more than mild aortic stenosis / regurgitation, with pacemakers, with other non-corrected congenital heart diseases (with the exception of bicuspid aortic valve) were excluded from the analysis. A semi-automated strain analysis was performed with speckle tracking technology and both global longitudinal strain (GLS) and MW were estimated using GE software™. Blood pressure was simultaneously measured in the patient's right arm. We specifically assessed: Global Work Index (GWI), Global Constructive Work (GCW), Global Work Waste (GWW) and Global Work Efficiency (GWE) Results: Twenty patients were included in the study, mean age of 36 ± 9 years, 30% males. Mean body surface area was 1.7. In this group of patients, 40% were hypertensives and in 55% there was a concomitant bicuspid aortic valve. Mean maximum aortic valve gradient was 11 mmHg and mean descending aortic gradient was 19 mmHg. Compared to recently published reference values for a normal population, repaired ACo patients had lower values of MW (Table). In multivariate linear regression analysis, independent predictors of GWI are systolic blood pressure (β=0.441) and let atrial volume indexed (LAVI) (β=0.507). For GCW, male gender (β=-0.605), LAVI (β=0.530) and diastolic blood pressure (β=-0.742). For GWE, the only predictor was LAVI (β=0.498) and no predictor was identified for GWW. The presence of bicuspid aortic valve, aortic valve gradient and descending aortic gradient did not have any influence in MW parameters, although higher aortic valve gradients were excluded from this study. Conclusion: Adult patients with repaired ACo, present lower MW indices and the main determinant for that difference are LAVI and blood pressure. GWW is the most independent parameter.